2014
DOI: 10.1039/c3ob42102c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of configuration of 2-vinyldiazocarbonyl compounds on their reactivity: experimental and computational study

Abstract: Non-fluorinated vinyldiazo compounds with trans-configuration irrespective of the nature of 3-R(1)-substituent (R(1) = H, Me, TBSO) even under ambient conditions easily cyclize to produce pyrazoles, while cis-stereoisomers undergo similar ring closure only at elevated temperatures or decompose to produce vinyloxocarbene reaction products. The 3-CF3-substituted analogues with cis- or trans-configuration do not produce pyrazoles at all, but on heating furnish only vinylcarbene derived products. DFT calculations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…By contrast, the development of new reactions triggered by their alkene motif is still challenging because many of the vinyldiazo reagents are prone to 1,5-electrocyclization to form pyrazoles if the diazo functionality cannot be rapidly decomposed. 37,38 This limitation also restricts their use in a radical reaction, even though vinyldiazo compounds can be considered as special types of alkenes. Although radical addition to vinyl azides and nitrogen extrusion to generate iminyl radicals is a well-known process, [39][40][41][42] surprisingly, an analogous method for the generation of vinyl radicals through radical addition to vinyldiazo reagents has been unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, the development of new reactions triggered by their alkene motif is still challenging because many of the vinyldiazo reagents are prone to 1,5-electrocyclization to form pyrazoles if the diazo functionality cannot be rapidly decomposed. 37,38 This limitation also restricts their use in a radical reaction, even though vinyldiazo compounds can be considered as special types of alkenes. Although radical addition to vinyl azides and nitrogen extrusion to generate iminyl radicals is a well-known process, [39][40][41][42] surprisingly, an analogous method for the generation of vinyl radicals through radical addition to vinyldiazo reagents has been unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…22 Mechanistically, the reaction likely follows an electrocyclic process, similar to the more highly studied vinyldiazomethane system, 23 with the initially formed enolate rearranging to the crystallographically observed more thermodynamically stable nitrogen anion before reacting with the acyl imine as shown in Scheme 11.…”
Section: Resultsmentioning
confidence: 91%
“…In the works by the Nikolaev group, it was shown that configuration of double bond in vinyldiazo compounds significantly affects their reactivity in this reaction ( Scheme 48 ) [ 100 , 101 ]. trans -Vinyl diazo compounds 196 readily underwent electrocyclization under moderate temperature (80 °C), while their cis -counterparts 198 produced pyrazoles 199 only at elevated temperatures (up to 120 °C) or decomposed with formation of furans 200 .…”
Section: Azoles With Two Heteroatomsmentioning
confidence: 99%